Analisis Kepuasan Pasien Terhadap Kualitas Pelayanan Di Unit Rawat Jalan Semen Padang Hospital: Analysis of Patient Satisfaction with the Quality of Outpatient Services at Semen Padang Hospital - Dendi Kurniawan; Heru Aulia Azman (Universitas Sumatera Barat, 2026)
Patient satisfaction is an important indicator for evaluating the performance and effectiveness of healthcare services. The quality of healthcare services is not only determined by the competence of medical personnel and the availability of facilities, but also by the ability of healthcare institutions to deliver services that meet patients’ expectations and needs. This study aims to analyze patient satisfaction with service quality in the Outpatient Unit of Semen Padang Hospital. This research employed a quantitative descriptive approach. The study population consisted of outpatients at Semen Padang Hospital, and the sampling technique used was accidental sampling, resulting in a total of 138 respondents. Data were analyzed using the Importance–Performance Analysis (IPA) and Potential Gain in Customer Value (PGCV) methods. The data processing was conducted using SPSS version 25 and Microsoft Excel. The results of the conformity level analysis indicate that 10 attributes fall into the hold category, while 12 attributes are classified in the action category, which require further attention for improvement and quality enhancement. The IPA results identified six attributes that fall into the main priority quadrant and therefore require immediate improvement. Furthermore, based on the PGCV analysis, attribute 18 was identified as the highest priority for improvement, with an index value of 4.62.